Tectonic classification of vertical crustal motions – a case study for New Zealand - TENZER, Robert; FADIL, Ali (Contributions to Geophysics and Geodesy, 2016)
We investigate the relationship between vertical crustal motion and tectonic block configuration. The study is conducted along the active tectonic margin between the Australian and Pacific tectonic plates in New Zealand with a well-defined tectonic block configuration. For this purpose, the rates of vertical crustal motions relative to the ITRF2008 reference frame are estimated based on processing the GPS data (provided by the GeoNET project) collected at 123 continuous and semi-continuous GPS sites. The numerical results confirmed the uplift of the central Southern Alps at the current rate of 4.5 mm/yr. This tectonic uplift is coupled in the South Island by the subsidence on both sides of the Southern Alps. The detected rates of subsidence in the eastern South Island are typically less than 1 mm/yr. The subsidence in the Buller Region (in the northwest South Island) is 1.4–1.5 mm/yr. Except for the Taupo Volcanic Zone and the upper Raukumara Block (in the central and northeast North Island), the subsidence is prevailing in the North Island. The systematic subsidence up to 9 mm/yr is detected along the Dextral Fault Belt (in the lower North Island). The largest localized vertical displacements (between −10 and 17 mm/yr) in the Taupo Volcanic Zone are attributed to active tectonics, volcanisms and geothermal processes in this region. A classification of these vertical tectonic motions with respect to the tectonic block configuration reveals that most of tectonic blocks are systematically uplifted, subsided or tilted, except for regions characterized by a complex pattern of vertical motions attributed to active geothermal and volcanic processes.